2004
DOI: 10.1095/biolreprod.103.023234
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-9 and Stem Cell Factor Promote Primordial Follicle Formation in the Hamster: Modulation by Follicle-Stimulating Hormone1

Abstract: Growth differentiation factor-9 (GDF-9) and stem cell factor (SCF) influence follicle formation beyond the primary stage; however, factors influencing the formation of primordial follicles remain elusive. To determine whether GDF-9 and SCF promoted primordial follicle formation during ovarian morphogenesis in the hamster, and whether FSH had any modulatory influence, fetal ovaries were collected on Gestation Day 15 from pregnant hamsters treated with or without an FSH antiserum on Gestation Day 12 and cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 17 publications
6
80
0
1
Order By: Relevance
“…Studies on growth factors have demonstrated that FSH and EGF are not essential for primordial follicle activation [24][25][26] but are important for latter follicle development [1,14]. On the other hand, GDF-9 and bFGF can promote the initiation of primordial follicle development and stimulate early preantral follicle growth [5,6,8,[27][28][29]. Hayashi et al reported that GDF-9 can enhance the effect of FSH on follicular growth [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on growth factors have demonstrated that FSH and EGF are not essential for primordial follicle activation [24][25][26] but are important for latter follicle development [1,14]. On the other hand, GDF-9 and bFGF can promote the initiation of primordial follicle development and stimulate early preantral follicle growth [5,6,8,[27][28][29]. Hayashi et al reported that GDF-9 can enhance the effect of FSH on follicular growth [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Both BMP15 and GDF9 are secreted by the oocyte early in ovarian differentiation, suggesting that signals from the oocyte to the granulosa cells are important for cyst breakdown and follicle formation (Elvin et al 2000). Supporting the involvement of GDF9 in follicle formation, addition of GDF9 to hamster ovaries in organ culture promotes the formation of follicles (Wang & Roy 2004). Mouse ovaries exposed to another TGFB family member, activin A, have an increased number of primordial follicles (Bristol-Gould et al 2006).…”
Section: Growth Factors and Signaling Moleculesmentioning
confidence: 98%
“…Ovary organ culture studies have revealed a potential role for stem cell factor (SCF) in primordial follicle formation. When SCF is added to neonatal hamster ovaries in organ culture, primordial follicle formation is accelerated while an antibody against SCF inhibits follicle formation (Wang & Roy 2004). SCF and its receptor, the c-KIT receptor tyrosine kinase, have been well studied during several phases of ovarian development.…”
Section: Growth Factors and Signaling Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…oocyte vs theca) cell types have diverse biological responses within the granulosa layer, the latter of which are mediated by the various type I receptors (ALKs) and intracellular Smad response proteins (Massague 1998, Mazerbourg et al 2004. Whether GDF-9 and BMP-4 have stimulatory effects on preantral follicular growth in cattle as they do in rodents (Vitt et al 2000b, Nilsson & Skinner 2002, Latham et al 2004, Wang & Roy 2004 and humans (Hreinsson et al 2002) awaits further elucidation. Also, whether GDF-9 plays a role in the regulation of ovulation rate in cattle, as recently demonstrated for sheep (Hanrahan et al 2004, Juengel et al 2004, will require additional research.…”
Section: ·05 4·3 17mentioning
confidence: 99%